PENGEMBANGAN PERANGKAT PEMBELAJARAN DENGAN MODEL IDEAL PROBLEM SOLVING BERBASIS MAPLE MATAKULIAH KALKULUS II - Eko Andy Purnomo; Akhmad Fathurohman (Universitas Muhammadiyah Semarang, 2014)
Calculus II or calculus integral is a compulsory course which must be taken in mathemathics program. This course is also become prerequisite for another course. based on the observation, the method used is expository which make the students’ skill and motivation are still low. The material for the course is already fixed and that should be changed is the teaching model. One of methods which can be developed is maple based of IDEAL problem solving. The purpose of the research is produce a valid and effective teaching aid. The development of devices learning which 4D models is designed and modified into 3D (define, design, develop) based on Thiagajaran and semmel theory. The result of the research showed that the (1) development of devices learning with maple based of IDEAL problem solving is valid, (2) the implementation of the teaching aid is effective, showed from the students’ (a) problem solving ability by itsstandard achievement criteria, (b) there is significant result on the improvement of skill in the process into the motivation of problem solving ability, (c) problem solving ability after the treatment show better result rather than before the treatment. However, it is suggested for thelecturer to apply the teaching model as an alternative to improve the motivation, processing skill, and problem solving ability.